Rhythm Gymnastics Modification Model for Family Fitness During The Covid 19 Pandemic - Wahyuningtyas Puspitorini; James Tangkudung (Universitas PGRI Palembang, 2022)
This study aims to create a Rhythm Gymnastics Modification Model for Family Fitness During the Covid 19 Pandemic. The ultimate goal of this study is to produce a modified model of rhythm gymnastics for fitness that can be used as a medium of exercise for families, helping families in maintaining fitness. Research time for 6 months from March to August 2021. This research was conducted in Jakarta. This research uses research and development (R&D) methods, with reference to the ADDIE model, where this research goes through 5 stages, namely Analysis, Design, Model Development, Implementation, and Evaluation. The initial product manufacturing using 25 model items, after validation by experts, there are 24 model items that are suitable for the Rhythm Gymnastics Modification Model for Family Fitness During the Covid 19 Pandemic. Based on data on the results of research that has been obtained from field tests as many as 24 items of Rhythm Gymnastics Modification Model for each family, and based on the results of research discussions, researchers can draw the conclusion that: Rhythm Gymnastics Modification Model made suitable for use by family fitness during the Covid 19 pandemic. This Rhythm Gymnastics Modification Model is then printed and used as a guidebook for the Rhythm Gymnastics Modification Model for each family. The results of the Rhythm Gymnastics Modification Model for Family Fitness During the Covid 19 Pandemic can provide a positive contribution for families and physical fitness observers specifically in carrying out physical activities for family fitness during the Covid 19 pandemic.